Surgical sponge associated with platelets rich plasma in skin mesh grafts and layer in rabbits (Oryctolagus cuniculus) - J.M. Pazzini; E.L. Serafim; R.R.A. Uscategui; V.T. Almeida; C.A.C. Oliva; F. Gärtner; I. Amorim; F. Faria; A. Rêma; N.P. Reis Filho; M.G.P.A. Ferreira; A.C. Silva; et al. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to evaluate of the efficacy of PRP employment associated with surgical sponges to improve the integration of the graft in the recipient bed. It was held at the Veterinary Hospital UNESP, Campus of Jaboticabal - SP, a study of 64 rabbits, divided into eight groups with eight animals. The groups were divided in control with saline solution 0,9%, control with PRP both without the sponge, surgical sponge with PRP, surgical sponge without PRP, and were used mesh and layer grafts in the respective groups. The data were submitted to statistical analysis (paired t-test, Kruskal-Wallis test, with subsequent use of the multiple comparison tests of Dunn, analysis of variance (F) test, Tukey test, P< 0.05). Edema and exudate with 3 and 3 and 7 days (P= 0,03 e P= 0,0049); coloring on the 14th day (P= 0,0001); cosmetic appearance on the 7th and 14th day (P= 0,0026 and P= 0,0001); mononuclear cells (P= 0,01) and polymorphonuclear (P= 0,01); fibroblast proliferation (P= 0,01); collagenous (P= 0,05); hemorrhage (P-007); necrosis and re-epithelialization (P= 0,2928 and P= 0,1). We concluded that the use of Platelet Rich Plasma Gel on skin grafts associated with a sponge as a compressive dressing promote the skin graft survival without a previous granulation tissue.